Hannah Arendt: Pendidikan Dan Natalitas - Sergius Lay (Pusat Riset dan Inovasi Nasional, 2024)
The background of this research is to explore Hannah Arendt's thoughts on the relationship between education and natality, which are generally summarized in a paper on education as an ethical event. The purpose of this research is to reveal Hannah Arendt's thought that education is related to how every student who comes before the educator is a fragile person, who needs an ethical attitude from the educators in treating them. Some of the core of Hannah Arendt's thoughts are first, phenomenology of action that not all actions in education can produce something good; second, education is an act of production that must produce something good; third, education as an action that cannot be predicted in advance, because of the new things brought by students and changing the face of the world; fourth, education as a story about formation that leads students into a world full of crises and being able to face them; fifth, a call to all humans to be responsible for caring for educational activities.